Computational study of the therapeutic properties of allicin and its nanocomplexes using DFT and molecular docking techniques - E. S. Mozafari; Mohammad T. Baei; E. Tazikeh Lemeski (Scientific Reports)
Abstract This study investigated the anti-inflammatory, anticancer, antiviral, and antibacterial effects of allicin and its complexes (Allicin/C₂₄, Allicin/B₁₂N₁₂, and Allicin/Al₁₂N₁₂) using advanced computational techniques such as Density Functional Theory (DFT), Quantum Theory of Atoms in Molecules (QTAIM), and molecular docking. The interactions were analyzed in two phases: gas and aqueous. Results revealed that the Allicin/Al₁₂N₁₂ complex exhibited the highest adsorption energy (Ead = -44.43 kcal/mol in the gas phase) and thermodynamic stability (ΔH = -44.36 kcal/mol, ΔG = -29.19 kcal/mol). QTAIM analysis revealed that the Allicin/C₂₄ complex involves very weak noncovalent interactions, the Allicin/B₁₂N₁₂ complex shows weak covalent bonding with considerable ionic character; and the Allicin/Al₁₂N₁₂ complex exhibits stronger covalent interactions with significant electron density sharing. The Allicin/Al₁₂N₁₂ complex showed a reduced energy gap (3.44 eV) and higher reactivity than free allicin (5.42 eV). Molecular docking demonstrated that this complex had the strongest binding affinity with biological targets, such as HER2, TNF-α, COVID-19 main protease, and Staphylococcus aureus. UV-Vis and IR spectroscopy revealed significant electronic and vibrational modifications in the complexes, particularly Allicin/Al₁₂N₁₂. These findings suggest that nanocages, especially Al₁₂N₁₂, can significantly enhance the stability, bioavailability, and therapeutic potential of allicin. The Allicin/Al₁₂N₁₂ complex, with its strong binding affinity and favorable electronic properties, has emerged as a promising candidate for treating cancer, inflammation, bacterial infections, and COVID-19. This study highlights the importance of natural products in drug discovery and the role of computational methods in understanding complex biological interactions.